Autophagy, cell death, and cancer - Lin, Lin (Mol Cell Oncol, 2015)
Autophagy is an evolutionarily conserved intracellular catabolic process that is used by all cells to degrade dysfunctional or unnecessary cytoplasmic components through delivery to the lysosome. Increasing evidence reveals that autophagic dysfunction is associated with human diseases, such as cancer. Paradoxically, although autophagy is well recognized as a cell survival process that promotes tumor development, it can also participate in a caspase-independent form of programmed cell death. Induction of autophagic cell death by some anticancer agents highlights the potential of this process as a cancer treatment modality. Here, we review our current understanding of the molecular mechanism of autophagy and the potential roles of autophagy in cell death, cancer development, and cancer treatment.